Enantiospecific, biosynthetically inspired formal total synthesis of (+)-liphagal. - George, J; Baldwin, J; Adlington, R (2010)
A biosynthetically inspired synthesis of (+)-liphagal has been achieved from (+)-sclareolide in 13 steps (9% overall yield). The key step is a biomimetic ring expansion of a highly stabilized benzylic carbocation, which generates the seven-membered ring and the benzofuran of the natural product in a single cascade reaction.